Evaluation of mortality attributable to SARS-CoV-2 vaccine administration using national level data from Qatar - Adeel A. Butt (3697705) (2023)
Accurate determination of mortality attributable to SARS-CoV-2 vaccination is critical in allaying concerns about their safety. We reviewed every death in Qatar that occurred within 30 days of any SARS-CoV-2 vaccine administration between January 1, 2021 and June 12, 2022. Probability of association with SARS-CoV-2 vaccination was determined by four independent trained reviewers using a modified WHO algorithm. Among 6,928,359 doses administered, 138 deaths occurred within 30 days of vaccination; eight had a high probability (1.15/1,000,000 doses), 15 had intermediate probability (2.38/1,000,000 doses), and 112 had low probability or no association with vaccination. The death rate among those with high probability of relationship to SARS-CoV-2 vaccination was 0.34/100,000 unique vaccine recipients, while death rate among those with either high or intermediate probability of relationship to SARS-CoV-2 vaccination was 0.98/100,000 unique vaccine recipients. In conclusion, deaths attributable to SARS-CoV-2 vaccination are extremely rare and lower than the overall crude mortality rate in Qatar. Other Information Published in: Nature Communications License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41467-022-35653-z